2003
DOI: 10.1038/sj.cgt.7700655
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-dead PKB gene therapy combined with hyperthermia for human breast cancer

Abstract: We have previously demonstrated that protein kinase B (PKB) is a mediator of heat-induced apoptosis for human breast cancer cells. To investigate the therapeutic potential of abrogating the function of this important survival protein, a novel replication-deficient adenovirus was constructed, wherein a mutant, kinase-inactive PKB gene (AAA) was inserted downstream of the CMV promoter. Two human breast cancer cell lines, MCF-7 and MDA-468, were treated, along with the MCF-10 serving as a ''normal'' mammary epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…DU145 and PC-3 prostate cancer cells and RKO colon carcinoma cells were obtained from American Type Culture Collection (2001,2001, and 2007, respectively) and cultured as previously described (17,18 , respectively, and were cultured as described previously (17)(18)(19)(20)(21)(22). MCF10A cells were a kind gift from Dr. Senthil Muthuswamy (2003; Ontario Cancer Institute/Princess Margaret Hospital, Toronto, Ontario, Canada) and were cultured as described previously either in full growth medium (23) or in growth factor withdrawal (0.05% horse serum, 10 μg/mL insulin) to downregulate endogenous MYC.…”
Section: Methodsmentioning
confidence: 99%
“…DU145 and PC-3 prostate cancer cells and RKO colon carcinoma cells were obtained from American Type Culture Collection (2001,2001, and 2007, respectively) and cultured as previously described (17,18 , respectively, and were cultured as described previously (17)(18)(19)(20)(21)(22). MCF10A cells were a kind gift from Dr. Senthil Muthuswamy (2003; Ontario Cancer Institute/Princess Margaret Hospital, Toronto, Ontario, Canada) and were cultured as described previously either in full growth medium (23) or in growth factor withdrawal (0.05% horse serum, 10 μg/mL insulin) to downregulate endogenous MYC.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also shown that inhibition of the PI3K/AKT pathway can significantly increase the sensitivity of hyperthermia 14 15…”
mentioning
confidence: 99%
“…Introduction of an Akt-kinase dead mutant directly into tumor cells can also inhibit tumor formation in nude mice (52). However, these effects were not observed in normal cells (53) or the MCF10 normal counterpart (52). Thus, Akt inhibition may not be toxic to normal cells.…”
Section: Discussionmentioning
confidence: 95%
“…They showed that the Akt inhibitor geldamycin and its clinically relevant derivative, 17-allyl amino-17-demethoxygeldamicin, led to inhibition of MCF-7 and tamoxifen-resistant MCF-7 tumor xenografts in severe combined immunodeficient mice. Introduction of an Akt-kinase dead mutant directly into tumor cells can also inhibit tumor formation in nude mice (52). However, these effects were not observed in normal cells (53) or the MCF10 normal counterpart (52).…”
Section: Discussionmentioning
confidence: 97%